Social Changes and Their Effects on Community-based Organizations’ Fundraising Efforts for Shan Displaced Communities in Thailand - Watchara Pechdin; Mokbul Morshed Ahmad (Journal of Mekong Societies, 2025)
Rapid social changes can significantly impact the fundraising efforts of community-based organizations (CBOs) by influencing donor priorities, shifting community needs, affecting social values, and increasing competition for limited resources. Forced displacement communities are particularly vulnerable to these challenges, as fundraising outcomes directly affect their livelihood security. This study explores the practical challenges faced by a CBO in Thailand as it fundraises for individuals from Shan state, Myanmar displaced by armed conflict. A deeper understanding of these challenges can help humanitarian aid agencies develop more effective strategies to support livelihood interventions for forced displacement communities. The thematic technique was employed to analyze qualitative data from seven in-depth interviews and direct participation in the fundraising. The study found that the CBO has been challenged by accusations of contributing to conflicts, ambiguous cross-border governance, and a rise in cyberattacks that disrupt funding sources and information flow. To address these issues, the study recommends fostering settings and conditions that build public trust and encourage technological collaboration to enhance fundraising success.